Antimicrobial Activity With Mixture Of Calcium Hydroxide And Propolis - CUEVAS-GUAJARDO SAHAMANTA; ARZATE-SOSA GABRIEL; FLORES- CHÁVEZ- ROSA ISELA; FABELA-GONZÁLEZ-LAURA V.; MENDIETA - ZERÓN - HUGO (International Journal of Pharma and Bio Sciences, 2011)
The aim of this study was to compare the in vitro antimicrobial activity of a mixture of calcium hydroxide/propolis, propolis/calcium hydroxide (Ca(OH)2) in Enterococcus faecalis, at different concentrations. Paper discs were impregnated with such medication and were placed in Mueller–Hinton plate agar with blood at 5 %, inoculating 1x105 UFC of E. faecalis and incubating at 35–37 oC for making measurements of the inhibition halos with a vernier at 24, 48 and 72 hours of incubation. The measurements were statistically analyzed with ANOVA with a p < 0.01 significance. The mixture of propolis and Ca(OH)2 1:3 at 48 and 72 hours showed the largest zone of inhibition.